Diagnosis and follow‐up of thrombotic thrombocytopenic purpura with an automated chemiluminescent ADAMTS13 activity immunoassay. Issue 1 (15th December 2020) - Beranger, Nicolas; Benghezal, Sandrine; Joly, Bérangère S.; Capdenat, Sophie; Delton, Adeline; Stepanian, Alain; Coppo, Paul; Veyradier, Agnès
Abstract: Background: Thrombotic thrombocytopenic purpura (TTP) is a life‐threatening thrombotic microangiopathy (TMA) caused by a severe functional deficiency in ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type I repeats‐13), the specific von Willebrand factor (VWF) cleaving protease. ADAMTS13 activity is essential to diagnose TTP but remains challenging to assess, as reference ADAMTS13 activity assays are manual and time consuming. Current techniques also lack robustness in low detectable ADAMTS13 activity range, which could prove problematic for therapy‐driven monitoring. Objectives: The HemosIL AcuStar ADAMTS13 activity assay is a fast, automated chemiluminescent assay, the performance of which remains to be evaluated prospectively on very large cohorts of patients with TMA and in real‐life conditions. Patients and Methods: Our study was conducted over two successive sequences: a retrospective evaluation followed by a "real‐life" prospective evaluation. Overall, we evaluated the HemosIL AcuStar ADAMTS13 activity assay on 539 citrated plasma samples. We extensively studied linearity, limit of detection, contamination, intra‐assay and interassay precisions with a specific focus on levels < 25 IU/dL. Diagnostic performances for the detection of < 10 IU/dL ADAMTS13 activity and overall method comparison were conducted with the fluorescence resonance energy transfer (FRETS)‐VWF73 assay as the reference method. Results: Technical performance proved excellent. Robustness in low detectable ADAMTS13 activity range was good, potentially qualifying this assay for therapy‐driven monitoring. Comparison with the FRETS‐VWF73 assay was satisfactory ( r 2  = .83, P  < .0001) as were the diagnostic performances for acute‐phase TTP (specificity, 99.7%; positive predictive value, 99.2%). Conclusion: The HemosIL AcuStar ADAMTS13 activity assay is a fast, reliable, automated technique well adapted as a first‐line ADAMTS13 activity assay for TTP diagnosis and follow‐up.